Efeitos do comportamento verbal sobre a ingestão de alimentos em crianças: regras e correspondência - Donadeli, Josiane Maria (2020)
The present doctoral dissertation was written in manuscript format. It consists of a summary of the dissertation in non-technical language, a theoretical essay, and three experiments. The theme addressed in this work is the effects of verbalization, from the experimenter and the individual, on the participants' food intake. The general objective was to verify if verbalizations would decrease the amount of unhealthy food eaten and if the use of an intermittent reinforcement schedule would promote the maintenance of this behavior. Three experiments were conducted, with children from 6 to 9 years old, and, in all sessions, nine pieces of healthy food (fruits and nuts) and nine pieces of unhealthy food (e.g., chocolate, cookies, packet snacks) were presented to them. In Experiment 1 it was examined the effect of a rule provided by the experimenter on the amount of the child's food intake. The rule signaled to child that they could eat only one piece of unhealthy food and as many as they wanted from healthy ones. There were no programmed consequences for following or not following the rule. Also, it was verified whether the rule presented by itself or accompanied by information of health and nutrition would have any effect on the responses. The results indicated that six out of the ten children decreased the amount of unhealthy food eaten during the rule presentation throughout the procedure, two children only decreased it at the beginning of the procedure, and two others did not change their behavior compared to the baseline. Furthermore, the presentation of the information did not change the responses, and all children increased unhealthy food intake when the rule was withdrawn. Experiment 2 aimed to verify whether the presentation of differential consequences for rule-following and, subsequently, its gradual withdrawal and its total suspension, would promote the maintenance of the behavior of eating less unhealthy food after removing the rule. For this, the children were told that they would earn one stamp, which could be exchanged for a prize, if they followed the rule. Otherwise, they would not earn the stamp. The consequences were provided in a continuous reinforcement schedule, then in intermittent reinforcement schedule, and, finally, they were no longer presented. The results showed that all children decreased the amount of unhealthy food intake when the rule was presented accompanied by the stamp, and five out of the seven children maintained their behavior after withdrawal the consequences. Finally, Experiment 3 examined the effect of a promise on unhealthy food intake. The child promised to eat no more than one piece of unhealthy food and as many as they wanted from healthy ones. The consequences were provided contingent only to the promise, and, as in the previous experiment, they were also withdrawn gradually, until their total suspension. The results indicated that the promise decreased the amount of unhealthy food eaten for five out of the six children. Two out of the six children were exposed to the correspondence training because they did not present correspondence between promise and eating. For them, the training was effective to promote correspondence and, consequently, reduced the amount of unhealthy food eaten. Five out of the six children maintained their behavior after removal of the consequences. Another interesting result was that there were children who increased the amount of healthy food eaten: two in experiments 1 and 2, and three in Experiment 3. The analyzes indicate that the rule changed the behavior, however, for higher effect and maintenance, the rule must be presented with differential consequences. Besides, the promise and correspondence training also increased the frequency of target behavior. Establishing operation is discussed as a variable that possibly influenced the responses.